Alternative dietary protein source for nile Tilapia: Giant African Snail (Achatina fulica, Ferussac, 1821) - Prasad, Archana; Chaudhary, Karishma (Our Nature, 2019)
The present study was conducted for two months between November 2019 and December 2019 to investigate the growth performance of Nile Tilapia fed with diets containing soyabean 100% (T1), soyabean and Achatina fulica: 50/50% (T2) and A. fulica 100% (T3). The experimental diets were formulated with 45% crude protein content. The stocking density was 30 fingerlings per tank of size 1m*1m*0.8m with three replications for each treatment. The tanks were stocked with the fingerlings of uniform size 9 ± 677 cm and weight 24 ± 0.66g. The experimental fishes were fed twice a day at 5% of their body weight. No significant differences (p˃0.05) in average weight gain, apparent feed conversion ratio (AFCR), daily weight gain, gross fish yield and net fish yield were observed. The study revealed that Giant African Snail (GAS) can be used either as partial or total replacement for soyabean as protein source for the fish. The use of harmful pest A. fulica in fish feed shows bright prospect in reducing the feeding expenses together with its suitable management.